Demarginalizing the intersection of race and sex: A black feminist critique of antidiscrimination doctrine, feminist theory and antiracist politics - Crenshaw, Kimberle (The University of Chicago Legal Forum, 1989)
Keywords: afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; droit; féminismes noirs; incontournable; intersectionnalité; militance; pol4212; premier cycle; projet charge mentale; racisme; ressource en ligne; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis

Kimberlé Crenshaw: The urgency of intersectionality | TED Talk - Crenshaw, Kimberlé (TedTalk, 2016)
Now more than ever, it's important to look boldly at the reality of race and gender bias – and understand how the two can combine to create even more harm. Kimberlé Crenshaw uses the term "intersectionality" to describe this phenomenon; as she says, if you're standing in the path of multiple forms of exclusion, you're likely to get hit by both. In this moving talk, she calls on us to bear witness to this reality and speak up for victims of prejudice.
Keywords: activisme; afro-féminisme; approches et analyses; com5170; cours; discipline; droit; droits civiques; droits des femmes*; droits humains; féminisme afroaméricain; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; science politique et droit; thématiques

Toward a race-conscious pedagogy in legal education - Crenshaw, Kimberle Williams (National Black Law Journal, 1988)
Keywords: afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; discipline; droit; fem9000; féminismes noirs; ressource en ligne; régions géographiques; science politique et droit; états-unis

Prison sexual abuse: Race, gender, and the rule of law - Buchanan, Kim (Columbia University, 2010)
In this dissertation, I argue that the exemption of prisons from the rule of law fosters abusive institutional practices that reveal the race and gender dynamics of sexual abuse in prison and in the outside world. The first article, Beyond Modesty: Privacy in Prison and the Risk of Sexual Abuse, shows that Fourth Amendment privacy offers little protection against the cross-gender searches and surveillance that expose women prisoners to sexual abuse by male guards. It proposes a reinterpretation of Fourth Amendment privacy that would recognize a constitutional right to be free from the fear, risk and reality of prison sexual abuse. The second article, Impunity: Sexual Abuse in Women's Prisons, shows that an edifice of constitutional, statutory and common-law rules confers near-complete institutional immunity against nearly all prisoner claims of custodial sexual abuse. These immunity rules parallel those of historical status regimes which excluded low-status litigants from courts on the basis of race and gender, such as civil death, slavery, segregation and the common law of marriage and rape–with similar results: low-status women of color are exposed to systematic and institutionalized sexual abuse, and are prevented from seeking protection or redress from the courts. The third article, Our Prisons, Ourselves: Race, Gender and the Rule of Law, develops these insights in men's prisons. In the absence of enforceable external rules, staff and administrators often adopt a gendered practice of institutional governance that requires prisoners to prove their manhood by fighting, and penalizes unmanly men by allowing others to rape them. These unlawful gendered practices are obscured by a false but powerful racialized narrative: most people inside and outside prison believe, inaccurately, that prison rape is mainly black-on-white. By casting sexual violence as a "complex and intractable" race relations problem for which administrators are not to blame, the racial narrative bolsters the rationale for exempting prison administration from the rule of law. Thus the perception (and reality) of unchecked prison violence supplies a reason for courts not to interfere with the unlawful institutional policies that foster it.
https://clio.columbia.edu/catalog/8481765
Keywords: approches et analyses; criminologie; discipline; droit; genre; intersectionnalité; mémoires/thèses; racisme; ressource en ligne; science politique et droit; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexuelles

Démarginaliser l’intersection de la race et du sexe : une critique féministe noire du droit antidiscriminatoire, de la théorie féministe et des politiques de l’antiracisme - Crenshaw, Kimberlé W. (Droit et société, 2021)
Dans cet article fondateur, K. Crenshaw introduit le concept d’« intersectionnalité », pour penser le caractère composé des effets de subordination liés à des facteurs comme la race, le genre, l’âge, la sexualité, etc. Elle analyse d’abord trois affaires juridiques qui ont traité des questions de discrimination raciale et sexuelle pour montrer les limites des « analyses à enjeu unique » : DeGraffenreid v. General Motors, Moore v. Hughes Helicopter, Inc. et Payne v. Travenol. Dans aucune de ces affaires, les tribunaux n’ont permis aux plaignantes d’alléguer une discrimination fondée à la fois sur la race et le sexe. K. Crenshaw montre qu’il faut penser l’intersectionnalité des discriminations pour saisir et corriger la situation particulière des femmes noires. Dans un second temps, elle élargit la réflexion vers le cadre sociopolitique et suggère que la condition des femmes noires doit être mieux prise en compte tant par les mouvements féministes que par les mouvements anti-racistes.
Première publication: 1989 https://www.cairn.info/revue-droit-et-societe-2021-2-page-465.htm
Keywords: amériques; antiracisme; approches et analyses; cours; discipline; droit; fem1000; incontournable; intersectionnalité; lit4700; militance; premier cycle; racisme; régions géographiques; science politique et droit; systèmes d'oppressions; thématiques; états-unis